IV Dexamethasone for Acute Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A randomized trial of dexamethasone 10 mg IV in 205 adult patients presenting with acute migraine to an emergency department (ED) found 25% of those with acute migrainebecame pain-free for at least 24 hours compared to 19% of those given placebo (p=0.34).